A cultura masculina e sua influência na soropositividade pelo HIV à AIDS - Pinheiro, Patrícia Neyva da Costa (2005)
During two decades of coexistence with the vírus of AIDS, we verified changes in the scenery of thís pandemic, mainly in relatíon to the population directly reached. At first, the risk groups existed, but these were substituted by the risk behaviors, and then the whole population started to be vulnerable, tends in view that the vulnerability includes the context social, cultural and political in which we are pari. Amid the dynamics of that pandemic we found an increase in the number of cases of AIDS in the heterosexual population, especíalíy, in the feminine whose vulnerability is directly harnessed to the masculino contamination. Conscious of the need to work with the heterosexual men in order to contribute in the prevention of AIDS, we aimed at to investigate in the masculine universe the values, perceptions, myths and faiths before the positive serum for HIV to AIDS. In the faith that the study of the masculine culture, as well as of other cultures, they need theoretical basement concerning the aspects that involve the culture, we decided to look for elucidation in the Information of some studious, like Hammersley and Atkinson (1994), Spradley (1980), Schawartzman (1993), Jonhson (1990), Geertz (1989, 1997, 2001) and Leininger (2001). Based in the ethnography and deliberate to contribute for the practice of the cultural care in the nursing we used ethnic-nursing with their steps for the. collection and analysis of the data, detaching the use of the model THE-P-R (Observation, participation and reflection) that was fundamental in the development of our study accomplished in the hospital and home context, where they were the heterosexual men. As a result of a slow and exhausting process of collect and analysis of the data, that it lasted approximately 17 months (we) built the followíng categories originated from the masculine universe: the infidelity, the vision of HIV, the masculine perception concerning the women and the masculine sexual behavior that associated amongst themselves, or no, they represented aspects that have influence on the way of seeing the world and of actirig of these men. We verified starting from the data that the cultural elements that created the categories of our study contributed for the non-valorization of the safe sex, increasíng the masculine vulnerability in relatíon to HIV and acting as potentiality to elevate the risk of contamination for HIV in the family. To the we contemplate concerning the discoveries, we considered to be necessary the development of works returned for the prevention close to the families, schools, units of health and broadcastings, having to the nursing, ín their several fields of performance, the possibility to guide the men, through cultural messages of their universe, for the prevention of HIV/AIDS.